REFRAMING WARTIME FINANCIAL PROPAGANDA: MEDIA, BEHAVIORAL COMMUNICATION, AND THE SAVING MOVEMENT IN JAPANESE-OCCUPIED JAVA (1942–1945) - Ardi Tri Yuwono; Andi Sebastian; Haru Rahman (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study reexamines the saving movement during the Japanese occupation of Java (1942–1945) by reframing it through contemporary perspectives on media, behavioral communication, and state-driven financial persuasion. Using historical methods combined with a systematic literature review, the research investigates how the Japanese administration orchestrated a multi-platform communication campaign through newspapers, magazines, radio broadcasts, films, songs, stage performances, and kamishibai to embed saving behavior into daily social routines. The novelty of this study lies in interpreting wartime financial propaganda as an early form of behavioral engineering, revealing patterns similar to today’s media convergence and state-controlled persuasive communication. The findings show that while propaganda messages successfully constructed narratives of duty, discipline, and economic nationalism, their effectiveness was limited by low public financial literacy and the reliance on coercive institutional mechanisms. By reframing historical propaganda through a modern behavioral lens, this study contributes to contemporary discussions on financial communication, media influence, and the ethics of state-led behavioral interventions.